Postpartum dönemde adölesanlara verilen üreme sağlığı eğitiminin etkinliği - Topatan, Serap (My University, 2012)
Postpartum Dönemde Adölesanlara Verilen Üreme Sağlığı Eğitiminin Etkinliği Araştırmamız, postpartum dönemde adölesanlara verilen üreme sağlığı eğitiminin etkinliğinin değerlendirilmesi amacıyla yarı deneysel ve prospektif olarak yapılmıştır. Çalışmamız Samsun Çarşamba Devlet Hastanesi’nde doğum yapan 15-19 yaş arası 120 adölesan (60 deney, 60 kontrol grubu) ile başlamıştır. Her 3 aylık periyodlarda olmak üzere 12 ay süresince izlem yapılmış, izlemlere tam olarak katılan 55 deney ve 46 kontrol grubu ile çalışmamız tamamlanmıştır. Araştırmanın sonucunda; deney (103.10±11.43) ve kontrol (99.15±9.53) grubunun eğitim öncesi üreme sağlığı bilgilerinin benzerlik gösterdiği belirlenmiştir. Eğitim sonrası deney grubunun Evli Kadınların Üreme Sağlığı Koruyucu Tutumlarını Belirleme Ölçeği (ÜSBÖ) toplam puan ortalaması 6.ayda 122.74±10.89, 12.ayda 119.98±11.79, kontrol grubunun ise 6.ayda 100.10±10.31, 12.ayda 99.52±10.47 olarak belirlenmiş ve aralarındaki fark istatistiksel olarak anlamlı bulunmuştur (p<0.001). ÜSBÖ toplam puanını etkileyen sosyo-demografik değişkenler çoklu regresyon analizi yapılarak değerlendirilmiş ve en çok etkileyen değişkenin yaş daha sonra eğitim durumu olduğu belirlenmiştir. Deney ve kontrol grubunun eğitim öncesi ve sonrası AP Tutum Ölçeği toplam puanları arasında istatistiksel olarak anlamlı bir fark bulunmuştur (p<0.001). Bu çerçevede, postpartum dönemde verilen üreme sağlığı eğitiminin ve yapılan izlemlerin adölesanların üreme sağlığı davranışlarını geliştirmede, AP tutumuna yönelik bilgi ve bilincin oluşmasında etkili olduğu ancak mevcut sağlık sisteminin destekleyici rolüne gereksinim duyulduğu sonucuna varılmıştır. lesan, aile planlaması, Evli Kadınların Üreme Sağlığı Koruyucu Tutumlarını Belirleme Ölçeği, postpartum dönem, üreme sağlığı.

The Efficiency of Reproduction Health Education Given to Adolescents during the Postpartum Period Our research, partly experimental and partly prospective, was conducted with the purpose of evaluating the efficiency of reproduction health education given to adolescents during the postpartum period. The study was made with 120 adolescents aged between 15 and 19 (60 experiment, 60 control group) who gave birth in Samsun Carsamba State Hospital. Follow-up was made every three months for a total of 12 months and the study was concluded with the complete participation of 55 individuals from the experiment group and 46 individuals from the control group. At the end of the research, it was found that the reproduction health knowledge of the experiment (103.10±11.43) and control (99.15±9.53) groups before education were similar. After education, the scale determining the reproduction health protective behavior of women total point averages was found to be 122.74±10.89 in the 6th month and 119.98±11.79 in the 12th for the experiment group, and 100.10±10.31 in the 6th month and 99.52±10.47 in the 12th month for the control group. The difference between them is statistically significant (p<0.001). The socio-demographic variables affecting the total points for the scale determining the reproduction health protective behavior of women were evaluated by multiple regression analysis, and the most effective variables found to be as age and education status. A statistically significant difference was also found between the total points for the family planning behavior scale of the experiment and control groups before and after education (p<0.001). From this, it was understood that reproduction health education given during the postpartum period and the follow-up have a positive effect on adolescents’ developing reproduction health behaviors and on creating knowledge and awareness related with family planning behavior, but that this requires the supportive role of the current health system. Key words: Adolescent, family planning, postpartum period, reproduction health, scale determining the reproduction health protective behavior of women.
Keywords: Kadın Hastalıkları ve Doğum